1991
DOI: 10.1002/elan.1140030618
|View full text |Cite
|
Sign up to set email alerts
|

A Potentiometric approach to the study of the antagonism between acetazolamide and I‐carnitine congeners on carbonic anhydrase activity

Abstract: The in vitro interactions among carbonic anhydrase (CA), acetazolamide (ACTZ), and some short chain acylcarnitines (l- and d-isomers) were studied by means of a recently developed potentiometric method of analysis, based on a pCO2 sensor. The l- and d-isomers of carnitine (C), acetylcarnitine (AC), propionylcarnitine (PC), and isobutyrrylcarnitine (iBC) were found not to affect CA catalytic activity in the absence of other compounds. Upon testing in the presence of ACTZ, the l-isomers of the carnitine congener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The fixation of carbon dioxide by zinc hydroxide and alkoxide complexes has received considerable attention in the past. This interest is aroused from the fact that such reactions are closely related to the mode of action of the enzyme carbonic anhydrase, which catalyzes the reversible hydrolysis of CO 2 according to the equation CO 2 + H 2 O ⇄ HCO 3 − + H + . , The active site of this enzyme consists of a zinc(II) center which is bound to three imidazole residues and a hydoxide ligand.…”
Section: Introductionmentioning
confidence: 99%
“…The fixation of carbon dioxide by zinc hydroxide and alkoxide complexes has received considerable attention in the past. This interest is aroused from the fact that such reactions are closely related to the mode of action of the enzyme carbonic anhydrase, which catalyzes the reversible hydrolysis of CO 2 according to the equation CO 2 + H 2 O ⇄ HCO 3 − + H + . , The active site of this enzyme consists of a zinc(II) center which is bound to three imidazole residues and a hydoxide ligand.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous analytical methods have been described in the literature to determine CRT in different biological samples such as chromatography [7; 8; 9; 10; 11], radiometry assays [9], electrophoresis [12; 13; 14], fluorimetry and spectrophotometry [15; 16], electrochemical assays with potentiometric [17; 18; 19], and amperometric [20] or Quartz-crystal microbalance transduction [21]. Overall, these methods are effective but unsuitable for point-of-care applications, where response time, portability and cost are critical.…”
Section: Introductionmentioning
confidence: 99%
“…Several analytical methods have been reported in the literature to analyze CRT in pharmaceutical formulations and in biological samples such as chromatographic techniques [16][17][18][19], capillary zone electrophoresis [20][21][22], fluorimetry [23], spectrophotometry [24], and electrochemical assays with potentiometric [25][26][27], amperometric [28] or quartz-crystal microbalance transduction [29]. Typically, separative methods, such as chromatographic and capillary zone electrophoresis, are accurate, precise and robust, but are unsuitable for routine applications for requiring high sample running times, organic solvents, pretreating sample procedures, expensive equipment, and high purity requirements for reagents.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional ionophores are ion exchangers and neutral macrocyclic compounds [25][26][27], but it has been shown that new materials that are complementary to the size and charge of a particular ion can lead to very selective interactions, thus enhancing the selectivity of the final device. This is the case of molecularly imprinted polymers (MIPs), by which polymeric materials are easily tailored with suitable selectivity for a guest compound [33,34].…”
Section: Introductionmentioning
confidence: 99%